Development of early maturing salt-tolerant rice variety KKL(R) 3 using a combination of conventional and molecular breeding approaches - Saminadane, Thirumeni; Geddam, Sathyadevi; Krishnaswamy, Paramasivam; Jothiganapathy, Karthick; Tamilselvan, Anandhan; Ramadoss, Bharathi Raja; Sri Hari Reddy, Patil; Singh, Uma Shankar; Singh, Rakesh Kumar; Platten, John Damien; Gregorio, Glenn B.; Singh, Nagendra Kumar; et al. (Frontiers in Genetics, 2024)
The development of seedling stage salinity tolerant rice variety is the primary objective of the study, which combines traditional breeding methods with marker-assisted breeding (MAB) approaches. Soil salinity poses a significant threat to rice production, causing stunted growth, leaf damage, and yield losses of up to 50% in severely affected areas. In this study, we introduced seedling stage salinity tolerance Quantitative Trait Locus (QTL) 'Saltol' from the salt-tolerant parent FL478 into the high yielding but salt sensitive/susceptible rice variety ADT 45 through combination of conventional and marker assisted breeding (MAB). Our multi-generational breeding process involves rigorous selection, screening, and physiological parameter assessments. KKL(R) 3 (KR 15066) emerged as the top performer in terms of salt tolerance among the Recombinant Inbred Lines (RILs). KKL(R) 3 emerged as the top performer among the Recombinant Inbred Lines (RILs), consistently demonstrating maximum mean grain yields under both salinity (3435.6±286.3 kg/ha) and normal (6421.8±174.2 kg/ha) conditions. In comparison to the early maturing, salt tolerant national check variety CSR 10, KKL(R) 3 showed a substantial yield increase ranging from 16 to 50%. This notable improvement positions KKL(R) 3 as a promising candidate for release, offering a reliable solution to maximize yields, ensuring food security, and promoting agricultural sustainability in both saline and non-saline environments. This study emphasizes the effectiveness of MAB in developing salt-tolerant rice varieties and highlights the significance of the Saltol QTL in enhancing seedling-stage salinity tolerance. The release of KKL(R) 3 has the potential to revolutionize rice production in salt-affected regions, offering farmers a reliable solution to maximize yields and contribute to food security while ensuring agricultural sustainability.